2020
DOI: 10.1016/j.jtcme.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Sulphate mineral waters: A medical resource in several disorders

Abstract: Based on their chemical composition, salus per aquam (spa) mineral waters (or medical mineral waters) can be classified as sulphurous, sulphate, bicarbonate etc. Sulphate mineral waters where the predominant element is sulphate anion SO 4 2− , are frequently used in clinical therapy. In this review, we describe and analyze the current scientific knowledge concerning the therapeutic effect of sulphate mineral waters in the treatment of several disorders. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…Another article published by Constantino et al in 2020 focused on sulfurous water as a medical resource in certain diseases. The authors concluded that daily ingestion of sulfurous-magnesium mineral water increased gastric secretion and stimulated its evacuation, modulating the motility and releasing the substances accompanying the digesting process (33).…”
Section: Evidence-based Literature Data Focused On the Benefit Of Crenotherapy For Gi (Gastrointestinal) Tract Pathologiesmentioning
confidence: 99%
“…Another article published by Constantino et al in 2020 focused on sulfurous water as a medical resource in certain diseases. The authors concluded that daily ingestion of sulfurous-magnesium mineral water increased gastric secretion and stimulated its evacuation, modulating the motility and releasing the substances accompanying the digesting process (33).…”
Section: Evidence-based Literature Data Focused On the Benefit Of Crenotherapy For Gi (Gastrointestinal) Tract Pathologiesmentioning
confidence: 99%
“…Sulphide waters contain much less total sulphur compared to sulphate waters, but they contain sulphur at lower levels of oxidation, especially divalent sulphur, which is the most biologically active [8].…”
Section: The Mechanism Of the Therapeutic Effect Of Radon-sulphide Watermentioning
confidence: 99%
“…Hydropinotherapy is a salus per aquam (Spa) treatment consisting of drinking quantities of mineral water at a definite temperature, according to specific prescriptions [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%